The Bilateral Deficit Phenomenon in Elbow Flexion: Explanations for Its Inconsistent Occurrence and Detection. Issue 1 (February 2022) - Beethe, Anne Z.; Flanagan, Shawn D.; Lovalekar, Mita; Fisher, Lee E; Nindl, Bradley C.; Connaboy, Christopher
The underlying mechanism(s) of the Bilateral Deficit (BLD) phenomenon is without consensus. Methodological inconsistencies across prior works may be an important source of equivocal results and interpretations. Based on repeatability problems with the BLD measure and maximal force definition, the presence or absence of the BLD phenomenon is altered, shifting conclusions of its mechanistic cause. Our purpose in this study was to examine methodological inconsistencies in applying the BLD measure to establish optimal methods for evaluating the underlying mechanism. Eleven healthy participants engaged in one familiarity and five test sessions, completing bilateral and unilateral elbow maximal voluntary isometric contractions. We defined maximal force by averaged and absolute peak and plateau values. BLD was evident if the bilateral index (BI), the ratio of the bilateral over summed unilateral forces, was statistically different from zero. We addressed interclass correlations (ICC), Chronbach's α, standard error of the mean, and minimal detectable change between and within sessions for all force measures and BI. We evaluated all combinations of sessions (i.e., 1–2, 3–5, 5–6) and maximal forces to establish the optimal number of sessions to achieve reliability. BLD was present for test sessions, but not for familiarization. All measures of maximal force were highly reliable between and within sessions (ICC(2, 1) ≥ .895). BI was only considered significantly reliable in sessions 3–5 ( p < .027), defined by absolute and average plateau forces, but reliability was still quantifiably poor (absolute: ICC(2, 1) = .392; average: ICC(2, 1) = .375). These results demonstrate that high force reliability within and between sessions does not translate to stable and reliable BI, potentially exposing the lack of any defined BLD mechanism.